Interaction of cationic phthalocyanines with DNA: Importance of the structure of the substituents - López Zeballos, Noelia del Carmen (2014)
The interaction of novel zinc (II) cationic phthalocyanines with CT-DNA was studied using absorption and fluorescence spectroscopy, as well as thermal denaturation profiles. Results showed an electrostatic interaction between the phthalocyanines and CT-DNA. The properties of these phthalocyanines were compared taking the structure of the macrocycle peripheral substituents into account. 2,9(10),16(17),23(24)-tetrakis[(N-butyl-N-methylammonium)ethylsulfanyl]phthalocyaninatozinc(II) tetraiodide (Pc6) had a greater affinity for the CT-DNA helix than its bioisoster 2,9(10),16(17),23(24)-tetrakis[(N-dibutyl-N-methylammonium)ethoxy]phthalocyaninatozinc(II) tetraiodide (Pc7). 2,9(10),16(17),23(24)-tetrakis[(2-trimethylammonium)ethyl-sulfanyl]phthalocyaninatozinc(II) tetraiodide (Pc13) also carried a sulfur atom like Pc6, but linked to bulky substituents such as trimethylammonium groups. The planar aromatic region of the cationic phthalocyanines in this study appears to be unable to facilitate their intercalation with CT-DNA.